Prevalence and genetic diversity of tick-borne encephalitis virus in ixodid ticks from specific regions of northwestern Russia. - Alena A Sharova; Nikolay K Tokarevich; Regina R Baimova; Olga A Freylikhman; Islam A Karmokov; Ekaterina G Riabiko; Gelena A Lunina; Roman V Buzinov; Olga V Sokolova; Lidia V Buts; Lubov A Bespyatova; Liliya A Bubnova; et al. (PLoS ONE)
Russia is a country with a high incidence of tick-borne encephalitis (TBE). In northwestern regions of Russia, 110 TBE cases were registered in 2021. The largest numbers of TBE cases were registered in the Arkhangelsk region and St. Petersburg. TBEV seropositivity among healthy individuals, including the unvaccinated population in northwestern Russia, was found in 12.2% of studied samples, indicating active TBEV circulation. The prevalence of TBEV is 2.4% in the two tick species most common in northwestern regions of Russia, Ixodes ricinus and Ixodes persulcatus. However, there is still no comprehensive data on the molecular characterization and phylogenetic analysis of the circulating TBEV strains. The purpose of the study was to determine the prevalence of TBEV and to identify its subtypes in ixodid ticks collected in specific areas of northwestern Russian regions. Phylogenetic analysis of E protein sequences of ten obtained strains showed that they all belong to the Siberian subtype, which were clustered into two groups: the most numerous Baltic group, clusteron 3D; and the Vasilchenko group. However, some unique isolates may form new clusterons.